Antiviral activity of hesperetin and naringenin against Chikungunya virus replication in vitro / Azin Ahmadi - Azin, Ahmadi (2018)
Chikungunya virus (CHIKV) is an emerging arbovirus, which has recently become globally important. It poses a progressive major impact on humankind in recent years, with possibly life-threatening and incapacitating arthritis. CHIKV infects human through the bite of mosquito vectors. National Institute of Allergy and Infectious Disease (NIAID) have classified CHIKV as Category C pathogen. It causes several clinical features similar to dengue virus infection, except that are associated with intense polyarthritis and tenosynovitis, where the similarities would usually cause misdiagnosis. Overall, millions of cases of CHIKV have been reported in over 50 countries. Currently, there is no available effective antiviral drug or vaccine has been developed for treatment of CHIKV infection. Treatment is usually symptomatically, with bed rest, fluids, and medicines to relieve symptoms of fever and aching. Thus finding and developing of lead compounds with anti-CHIKV activity that could be further developed to a practical treatment is urgently required. Several studies have reported the wide-ranging antiviral activities of flavanones; however, an inhibitory effect of selected compounds yet to be shown against CHIKV. Flavanones are polyphenol specific of citrus fruits, where they are naturally present in high amounts and part of human diet almost exclusively. In this study, we investigated the antiviral properties of two types of flavanones namely, naringenin and hesperetin against CHIKV in vitro replication. Our data have shown dose dependent inhibitory effects for naringenin and hesperetin against CHIKV intracellular replication using different assays including, CHIKV replicon cell line, time of addition and virus yield assay. MTS assay was performed to determine the cytotoxicity of hesperetin and naringenin on Vero and BHK cell lines. Antiviral iv activity of the compounds was further investigated by evaluation of CHIKV protein expression using quantitative immunofluorescence assay and Western blotting. Briefly, these compounds presented significant antiviral activity against CHIKV, reducing both CHIKV replication efficiency and down-regulating production of viral proteins involved in replication. Naringenin with IC50=6.818 ?M (SI=80.27) and hesperetin with IC50=8.500 ?M (SI=23.34) inhibited the post entry stages of CHIKV replication activity. The replication efficiency of CHIKV at each antiviral assay was revealed by using the qRT-PCR assay with RNA copy number as guideline. In conclusion, data obtained from the current study suggest that naringenin and hesperetin could be potential candidates to be developed further as anti-CHIKV therapeutic agents. This study may have significant outcome to broaden the chance of discovering the effective antiviral agent for CHIKV infection.